Optimize capacity for a uniform waste transportation collection - Silva, J. T.; Oliveira, A. F.; Martins, A. L.; Ferreira, J. C. (Intelligent Transport Systems: From Research and Development to the Market Uptake. Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2019)
Transportation-related costs are responsible for a large portion of the waste collection process. In the past several optimization approaches in routing having been the proposal with a diversity of algorithm. In this work we propose a novel approach where we analyze waste deposition volume and try to identify patterns for a deterministic and uniform waste collection. Instead of routing optimization we propose a capacity determination based on location, year period, special events and weather conditions. An IoT sensor transmitted volume every time the wasted door is open and provide real-time value.